Tibetan Medicine Duoxuekang Capsule Ameliorates High-Altitude Polycythemia Accompanied by Brain Injury - Chen, Ke; Li, Ning; Fan, Fangfang; Geng, ZangJia; Zhao, Kehui; Wang, Jing; Zhang, Yi; Tang, Ce; Wang, Xiaobo; Meng, Xianli (Frontiers in Pharmacology, 2021)
Objective: Duoxuekang (DXK) capsule is an empirical prescription for Tibetan medicine in the treatment of hypobaric hypoxia (HH)-induced brain injury in the plateau. This study aimed to investigate the protective effects and underlying molecular mechanisms of DXK on HH-induced brain injury. Methods: UPLC–Q-TOF/MS was performed for chemical composition analysis of DXK. The anti-hypoxia and anti-fatigue effects of DXK were evaluated by the normobaric hypoxia test, sodium nitrite toxicosis test, and weight-loaded swimming test in mice. Simultaneously, SD rats were used for the chronic hypobaric hypoxia (CHH) test. RBC, HGB, HCT, and the whole blood viscosity were evaluated. The activities of SOD and MDA in the brain, and EPO and LDH levels in the kidney were detected using ELISA. H&E staining was employed to observe the pathological morphology in the hippocampus and cortex of rats. Furthermore, immunofluorescence and Western blot were carried out to detect the protein expressions of Mapk10, RASGRF1, RASA3, Ras, and IGF-IR in the brain of rats. Besides, BALB/c mice were used for acute hypobaric hypoxia (AHH) test, and Western blot was employed to detect the protein expression of p-ERK/ERK, p-JNK/JNK, and p-p38/p38 in the cerebral cortex of mice. Results: 23 different chemical compositions of DXK were identified by UPLC–Q-TOF/MS. The anti-hypoxia test verified that DXK can prolong the survival time of mice. The anti-fatigue test confirmed that DXK can prolong the swimming time of mice, decrease the level of LDH, and increase the hepatic glycogen level. Synchronously, DXK can decrease the levels of RBC, HGB, HCT, and the whole blood viscosity under the CHH condition. Besides, DXK can ameliorate CHH-induced brain injury, decrease the levels of EPO and LDH in the kidney, reduce MDA, and increase SOD in the hippocampus. Furthermore, DXK can converse HH-induced marked increase of Mapk10, RASGRF1, and RASA3, and decrease of Ras and IGF-IR. In addition, DXK can suppress the ratio of p-ERK/ERK, p-JNK/JNK, and p-p38/p38 under the HH condition. Conclusion: Together, the cerebral protection elicited by DXK was due to the decrease of hematological index, suppressing EPO, by affecting the MAPK signaling pathway in oxidative damage, and regulating the RAS signaling pathway.